Comparative Study of Outcome in Cessation Therapy of Smoked Form of Tobacco and Factors Affecting It Using Tablet Bupropion or Nicotine Replacement Therapy - Gaurav Ekanath Pawar; Sarika Dakshikar; Poornima Khadanga (Annals of Indian Psychiatry, 2024)
Background: Tobacco use is one of the major causes of preventable deaths and diseases in India. Standard treatment used in tobacco use disorder can be broadly categorized as nicotine replacement therapy (NRT) and nonnicotine pharmacotherapy. Aims: The aim of this study was to compare the outcome of tobacco cessation in subjects using the smoked form of tobacco, using tablet bupropion or NRT, and to assess various factors influencing the outcome. Settings and Design: Twelve-week follow-up study was conducted in patients of tobacco use disorder attending the outpatient department of psychiatry in a tertiary care teaching institute for a duration of 12 months, after permission from the institutional ethical committee. Materials and Methods: Hundred subjects were taken as per the inclusion criteria. After obtaining the general sociodemographic data, the severity of tobacco dependence was assessed by Fagerstrom Scale at baseline, 2 weeks, 4 weeks, 8 weeks, and 12 weeks after assigning intervention (tablet bupropion or NRT) of their choice. Statistical Analysis Used: SPSS software is used for statistical analysis. Pearson correlation, analysis of variance, and multiple regression analysis were done and P < 0.05 was considered to be significant. Results and Conclusion: NRT works better in all groups of patients having mild, moderate, or severe tobacco dependence, whereas bupropion works better in groups of patients having moderate-to-severe tobacco dependence.